Comparative study of different fuel cell technologies - Mekhilef, Saad; Saidur, Rahman; Safari, Azadeh (Elsevier, 2012)
Fuel cells generate electricity and heat during electrochemical reaction which happens between the oxygen and hydrogen to form the water. Fuel cell technology is a promising way to provide energy for rural areas where there is no access to the public grid or where there is a huge cost of wiring and transferring electricity. In addition, applications with essential secure electrical energy requirement such as uninterruptible power supplies (UPS), power generation stations and distributed systems can employ fuel cells as their source of energy. The current paper includes a comparative study of basic design, working principle, applications, advantages and disadvantages of various technologies available for fuel cells. In addition, techno-economic features of hydrogen fuel cell vehicles (FCV) and internal combustion engine vehicles (ICEV) are compared. The results indicate that fuel cell systems have simple design, high reliability, noiseless operation, high efficiency and less environmental impact. The aim of this paper is to serve as a convenient reference for fuel cell power generation reviews.